Implementasi Peraturan Bupati Pesawaran Nomor 35 Tahun 2017 tentang Pengelolaan Kawasan Wisata Bahari dalam Perspektif Siyāsah Tanfīdziyyah - Rian Hidayat; Iskandar Syukur; Muhammad jayus (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze the implementation of the Regent Regulation of Pesawaran Regency concerning the management of marine tourism areas from the perspective of Siyāsah Tanfīdziyyah. Marine tourism has significant potential in supporting regional economic development, increasing community welfare, and preserving coastal environmental sustainability. However, the management of marine tourism requires effective government policies and active participation from stakeholders to ensure the realization of public benefit (maṣlaḥah ʻāmmah). This research employed a qualitative approach with a case study design conducted in Pesawaran Regency, Lampung Province. Data were collected through observation, interviews, and documentation, then analyzed descriptively using data reduction, data presentation, and conclusion drawing techniques. The findings reveal that the implementation of marine tourism management policies in Pesawaran Regency has been carried out through planning, organizing, and implementation stages involving the local government, local communities, and business partners. The development of marine tourism contributes to improving the local economy and optimizing regional tourism potential. From the perspective of siyāsah tanfīdziyyah, the role of the local government reflects the implementation of executive authority in managing public interests, environmental sustainability, and social welfare in accordance with the principles of justice and public benefit in Islamic governance.